Subharmonics in the solutions of a model of the song motor nuclei in songbirds - Jercog, Pablo (2005)
Songbirds produce their vocalizations by means of a vocal organ called syrinx. A relatively small number of parameters are cyclically changed in order to produce a song. These time-dependent parameters are generated by a set of hierarchically organized neural nuclei. In this work we use theoretical tools in order to test the hypothesis that some aspects of the phrase structure in a song can be the result of the nonlinear response of some of these nuclei to a basic regular syllabic oscillation. We propose simple rate models for the activities displayed by the nuclei and inspect their dynamics.